Capsaicin, a Phytochemical From Chili Pepper, Alleviates the Ultraviolet Irradiation-Induced Decline of Collagen in Dermal Fibroblast via Blocking the Generation of Reactive Oxygen Species - Wu, Qiyun; Bai, Panzhu; Guo, Hongsheng; Guo, Maggie S. S.; Xia, Yingjie; Xia, Yiteng; Gao, Xiong; Wang, Xiaoyang; Wu, Jiahui; Dong, Tina T. X.; Tsim, Karl W. K. (Frontiers in Pharmacology, 2022)
Capsaicin, a major ingredient in chili pepper, has broad pharmaceutical applications, including relieving pain, anti-inflammation, and treating psoriasis. In dermatological biology, capsaicin has been shown to prevent the ultraviolet (UV)-induced melanogenesis via TRPV1 receptor. To strengthen the roles of capsaicin in skin function, the damaged skin, triggered by exposure to UV, was reversed by capsaicin in both in vitro and in vivo models. In cultured dermal fibroblasts, the exposure to UV induced a decrease of collagen synthesis and increases expression of matrix metalloproteinases (MMPs), generation of reactive oxygen species (ROS), and phosphorylation of Erk and c-Jun, and these events subsequently led to skin damage. However, the UV-mediated damages could be reversed by pre-treatment with capsaicin in a dose-dependent manner. The effect of capsaicin in blocking the UV-mediated collagen synthesis was mediated by reducing generation of ROS in dermal fibroblasts, instead of the receptor for capsaicin. Hence, capsaicin has high potential value in applying as an agent for anti-skin aging in dermatology.